2010
DOI: 10.7326/0003-4819-152-9-201005040-00009
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-analysis: Noninvasive Ventilation in Acute Cardiogenic Pulmonary Edema

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0
28

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(126 citation statements)
references
References 42 publications
2
91
0
28
Order By: Relevance
“…[2][3][4][5][6] NIV is also used for managing respiratory symptoms associated with acute cardiogenic pulmonary edema, and minimizes SEE THE RELATED EDITORIAL ON PAGE 303 the need for intubation in these patients. 7 Investigators have also used NIV in asthma, pneumonia, neuromuscular disease, post-extubation, and hypoxemic and postoperative acute respiratory failure, with varying success. [8][9][10][11][12][13][14][15] The timing and location of initiation of NIV has been evaluated by investigators.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] NIV is also used for managing respiratory symptoms associated with acute cardiogenic pulmonary edema, and minimizes SEE THE RELATED EDITORIAL ON PAGE 303 the need for intubation in these patients. 7 Investigators have also used NIV in asthma, pneumonia, neuromuscular disease, post-extubation, and hypoxemic and postoperative acute respiratory failure, with varying success. [8][9][10][11][12][13][14][15] The timing and location of initiation of NIV has been evaluated by investigators.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for acute cardiogenic pulmonary edema there is a significant reduction in the intubation rate with NIV (risk ratio 0.54, 95% CI 0.33-0.86). 8 Although more patients (10%) are intubated with usual medical care, still 5% of patients required intubation despite the use of NIV. A prospective observational study of NIV use in France reported a 38% failure rate in a mixed population of patients with acute respiratory failure.…”
Section: The Problemmentioning
confidence: 99%
“…A number of narrative and systematic reviews have been written on this subject. [1][2][3][4][5][6][7][8] For some conditions, such as exacerbation of COPD or acute cardiogenic pulmonary edema, the use of NIV is considered first-line therapy and standard of care. In fact, an entire RESPIRATORY CARE Journal Conference was recently devoted to this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients do not tolerate the mask due to claustrophobia or other causes, and nasal bridge skin breakdown can occur and difficult the use of NIV. Non-invasive ventilation is now considered as a firstline intervention in selected patients with severe exacerbation of chronic obstructive pulmonary disease (COPD) and hypercapnic respiratory failure (4,5), and those affected of acute cardiogenic pulmonary oedema (CPO) (6). Immunosuppressed patients have poor outcome when they develop pulmonary infiltrates and hypoxemic ARF; in these patients, NIV seems to decrease the needs for intubation and the related morbidity and mortality (7,8).…”
Section: Introductionmentioning
confidence: 99%